Determinants of Investment Grade Status in Emerging Markets - Jaramillo, Laura (Washington, D.C. : International Monetary Fund, 2010)
Emerging market countries seek investment grade status to lower financing costs for the sovereign, expand the pool of potential investors to institutional investors, and allow corporates the possibility of reducing their borrowing costs. Using a random effects binomial logit model on a sample of 48 emerging markets, the paper finds that, to a large extent, investment grade rating assignments can be explained by a handful of variables. The results also suggest that efforts by emerging markets to increase the likelihood of an upgrade should focus on debt indicators rather than the other key determinants of investment grade status.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet